2022
DOI: 10.1002/da.23237
|View full text |Cite
|
Sign up to set email alerts
|

Absence of early mood improvement as a robust predictor of rTMS nonresponse in major depressive disorder

Abstract: Background: Symptoms of major depressive disorder (MDD) are reported to change early in treatment with repetitive transcranial magnetic stimulation (rTMS). We evaluated early changes in sleep, anxiety, and mood as predictors of nonresponse to rTMS treatment.Methods: Three hundred twenty-nine subjects with nonpsychotic MDD completed a 6-week course of rTMS treatment. Subjects were stratified by the severity of their baseline depression, and had their overall depressive symptoms recorded every week of treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Lower HamD scores after 10 sessions appear predictive of remission, indicating that remitters tend to show improvements early into their treatment timeline. By 20 sessions, lower HamD, SDS, and BAI scores are positive predictors of remission and response (Table 2), in line with previous findings that significant differences in response and remission can be detected before the end of a full course of treatment 44,45 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lower HamD scores after 10 sessions appear predictive of remission, indicating that remitters tend to show improvements early into their treatment timeline. By 20 sessions, lower HamD, SDS, and BAI scores are positive predictors of remission and response (Table 2), in line with previous findings that significant differences in response and remission can be detected before the end of a full course of treatment 44,45 …”
Section: Discussionsupporting
confidence: 89%
“…By 20 sessions, lower HamD, SDS, and BAI scores are positive predictors of remission and response (Table 2), in line with previous findings that significant differences in response and remission can be detected before the end of a full course of treatment. 44,45 We found no correlation between the baseline anxiety scores as measured by BAI in either treatment outcome. One previous study found that baseline high anxiety was associated with a lower chance of remission, 42 however the assessment scale used (Brief Symptom Inventory-Anxiety Subscale [BSI-A]) differed from the one used in our study (BAI).…”
Section: Demographicsmentioning
confidence: 61%
“…Next, absolute activity power in the alpha (8-12 Hz) and low-gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) bands was extracted, and asymmetric activity scores were calculated as ratio between activity power of each electrode and that of the homologous electrode in the counter hemisphere. Alpha, low-gamma, and low-gamma/alpha ratio of activity and asymmetry scores were then linearly correlated with improvement percentage in HDRS21 score following 6 weeks of treatment.…”
Section: Eeg Recording and Statistical Analysismentioning
confidence: 99%
“…For example, symptom clusters derived from individual items on rating scales have been used to differentiate between patients' responses to pharmaceutical treatments for depression (28,29). Some success has been made while applying this approach to differentiate between TMS protocols, with data from early response after several treatment sessions but not at the pre-treatment baseline (30)(31)(32)(33). In addition, several attempts at identifying biomarkers of pharmaceutical and TMS efficacy have been made based on neuroimaging data, primarily from functional magnetic resonance imaging (MRI) and electroencephalogram (EEG) recordings (11, 12, 34-6 36).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of ten sessions was determined as follows: Feffer et al [ 49 ] showed that, among individuals with MDD, early symptom improvements after ten sessions predicted the overall outcome of rTMS interventions. Similarly, an early response to rTMS was associated with clinical improvements among individuals with MDD [ 50 ], while an early non-response to rTMS was associated with an overall non-response to rTMS [ 51 ]. Höppner et al [ 22 ] observed an antidepressant efficacy of rTMS interventions after 10 out of 12 days.…”
Section: Interventionsmentioning
confidence: 99%